Validity and reliability of the Chinese version of the Break-up Distress Scale for college students - Qiao, Xin; Zhan, Tingting; Geng, Yaoguo (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to revise the validity and reliability of the Chinese version of the Break-up Distress Scale (BDS) for college students.MethodsA total of 669 college students with breakup experience in the last 6 months were selected using the online survey platform Questionnaire Star and randomly divided into two groups: Sample 1 for exploratory factor analysis (EFA) and Sample 2 for confirmatory factor analysis (CFA). Depression, anxiety, and sleep subscales of the DSM-5 Self-Rated Level 1 Cross-Cutting Symptom Measure-Adult were used as criterion tools.ResultsThe EFA supported the one-dimensional model of the original scale. The CFA showed that the model structure fit well (χ2/df = 1.792, GFI = 0.935, AGFI = 0.915, NFI = 0.958, RMSEA = 0.048). Cronbach’s α of the BDS was 0.964, and the total score of the scale was significantly and positively correlated with the criterion scales. The scale demonstrated strict equivalence across genders and breakup initiators. Males’ scores were significantly higher than those of females, and the break-up distress scores of breakup initiators were significantly lower than those of dumped people.ConclusionThe Chinese version of the BDS can be used to assess distress in Chinese college students. The scale has satisfactory reliability and validity.